2004
DOI: 10.1016/j.femsle.2004.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Intragenomic heterogeneity of the 16S rRNA–23S rRNA internal transcribed spacer amongPseudomonas syringaeandPseudomonas fluorescensstrains

Abstract: The 16S-23S rRNA internal transcribed spacer regions (ITS1) from 14 strains of Pseudomonas syringae and P. fluorescens were sequenced. ITS1 exhibited significant sequence variability among different operons within a single genome. From 1 to 4 types of ITS1 were found in individual genomes of the P. syringae and P. fluorescens strains. A total of eight ITS1 types were identified among strains studied. The ITS1 nucleotide sequences consisted of conserved blocks including, among others, a stem-forming region of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 19 publications
(41 reference statements)
3
18
0
Order By: Relevance
“…The locations of the amplicons derived from both the E. coli and F. graminearum contaminants in these profiles were confirmed by comparison with the RISA profiles of DNA directly prepared from these microbes (data not shown). The multiple fragments derived from E. coli most likely reflect the intragenomic variation in ribosomal rRNA gene operons, as reported for several bacteria including E. coli 35) .…”
Section: Resultssupporting
confidence: 53%
“…The locations of the amplicons derived from both the E. coli and F. graminearum contaminants in these profiles were confirmed by comparison with the RISA profiles of DNA directly prepared from these microbes (data not shown). The multiple fragments derived from E. coli most likely reflect the intragenomic variation in ribosomal rRNA gene operons, as reported for several bacteria including E. coli 35) .…”
Section: Resultssupporting
confidence: 53%
“…ITS1 varies considerably among different operons (Naimi et al, 1997;Gurtler, 1999;Iteman et al, 2000) without a remarkable length difference. In the genus Pseudomonas, intercistronic heterogeneity of the ITS1 reported to date is primarily due to insertions and/or deletions of nucleotide blocks outside the tRNA genes (Milyutina et al, 2004;Natalini & Scortichini, 2007). Milyutina et al (2004) identified eight ITS1 types among 14 strains of P. syringae and P. fluorescens with similar sequence lengths except for one strain exhibiting about 8 % length difference among its copies.…”
Section: Discussionmentioning
confidence: 99%
“…Smith et al (1999) demonstrated the presence of two different ITS1 types in Pseudomonas fluorescens strain F113, and Pseudomonas putida strain KT2440 was reported to have seven rRNA operons with non-identical ITS1 sequences (Nelson et al, 2002). One to four types of ITS1 were found in individual genomes of Pseudomonas syringae and P. fluorescens strains (Milyutina et al, 2004). However, none of the reported intercistronic heterogeneity of ITS1 among Pseudomonas strains was due to excessive deletions within the tRNA Ile and tRNA Ala regions; in most cases it appeared to be due to recombination and horizontal transfer of variable nucleotide blocks outside the tRNA genes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As one of the potential biases in RISA, Milyutina et al (2004) have demonstrated in their previous report that intragenomic differences in the IGS in some cases exceed the differences in these sequences among strains. This could bias the interpretation of both the quantitative and qualitative interpretation of the data obtained by RISA.…”
Section: Ribosomal Intergenic Spacer Analysis (Risa)mentioning
confidence: 99%